Simulation of a non-linear interaction in the combined magnetron - Frolova, T. I.; Churyumov, G. I. (IEEE, 2000)
In the last few years the development of efficient crossed-field tubes has been connected with the creation of new non-traditional designs. In this paper a mathematical model of a new combined magnetron and the features of its operation modes are discussed.
Keywords: nonlinear interaction simulation; combined magnetron; crossed-field tubes; mathematical model